Optimal OCR coordination in a high penetration distribution power system using a refined immune algorithm with an auto-tuning reproductive mechanism - Tung-Sheng Zhan; Yih-Der Lee; Jheng-Lun Jiang (AIMS Energy)
Integrating an increasing number of distributed energy resources into medium-voltage and low-voltage radial distribution networks is causing significant shifts in power flow and fault current distribution. These changes introduce new challenges for power system protection coordination. We present an adaptive protection coordination strategy designed to address these challenges. The proposed approach involved tracking the connectivity of the system structure to establish a relay numbering sequence, which served as a tracking route. These routes were further categorized into main feeder and branch paths based on the system topology. The strategy to optimize the operation time of overcurrent relays involved adjusting the time multiplier setting (TMS) and pickup current setting (PCS) for each relay, focusing on improving relay coordination. The coordination problem was formulated to minimize the total operation time of both primary and backup relays while adhering to coordination time interval (CTI) constraints. A refined immune algorithm, augmented with an auto-tuning reproductive mechanism, was proposed to determine the optimal time multiplier settings and pickup current settings parameters along the tracking route. We used a 16-bus actual distribution network and the IEEE 37 Bus system with distributed generators to evaluate the effectiveness of the proposed adaptive protection coordination. The results demonstrated that the proposed algorithm significantly reduced overall operation time and mitigated the impact on protection coordination settings following the integrations. Furthermore, a comparative analysis with other metaheuristic algorithms highlighted the superior efficiency and performance of the proposed approach.